2004
DOI: 10.1002/ptr.1488
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antioxidant activity and phenolic content of three lichen species

Abstract: The antioxidant activities (AA), reducing powers (RP) and total phenolic contents (TPC) of methanol and water extracts of three lichen species, Usnea longissima Ach., Usnea florida (L.) Weber ex Wigg. and Lobaria pulmonaria (L.) Hoffm. were determined in vitro. Of the extracts tested, the methanol extracts of Lobaria pulmonaria and Usnea longissima showed potent antioxidant activities. The methanol extract of L. pulmonaria also had the highest total phenolic contents (87.9 mg/g lyophylisate). For the methanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(87 citation statements)
references
References 17 publications
(16 reference statements)
5
79
1
2
Order By: Relevance
“…In most lichens, phenols including depsides, depsidones and dibenzofurans are, important components with antioxidant activity [7,9,27]. In this study, we found that the content of phenol in the methanol extract of different species is very different.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In most lichens, phenols including depsides, depsidones and dibenzofurans are, important components with antioxidant activity [7,9,27]. In this study, we found that the content of phenol in the methanol extract of different species is very different.…”
Section: Discussionmentioning
confidence: 73%
“…Consequently, an alternative solution is to use naturally occurring antioxidants as additives in food as well as traditional medicines [3][4][5]. In accordance with identifying a suitable natural antioxidant, the antioxidant activity of many organisms has been demonstrated which includes some species of lichens [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is a good correlation between flavonoid compounds of the tested extracts and free radical scavenging activity, reducing power and superoxide anion radical scavenging (r=0.92, r=0.81 and r=0.74). Previous researches also showed a high correlations between antioxidative activities and phenolic content (Odabasoglu et al 2004;Hodzic et al 2009). The strong relationships between total phenolic contents of tested extracts and the antioxidative activities suggest that phenolics might be the major antioxidant compounds in studied extracts.…”
Section: Correlations Between Total Phenolic Content and Antioxidativmentioning
confidence: 87%
“…Numerous researches reported a significant correlation between antioxidative activities of lichens and phenolic content (Behera et al 2009;Ranković et al 2012). However, some authors believe that the antioxidant activity of extracts may not necessarily correlate with the content of polyphenolics (Odabasoglu et al 2004), suggesting that the antioxidant activity of different lichens may also depend on other, non-phenol components. Gulcin et al (2002) investigated aqueous extract of C. islandica which showed effective reducing power, superoxide anion radical scavenging and free radical scavenging activities.…”
Section: Resultsmentioning
confidence: 99%